Review on Development of a New Energy Efficient Opportunistic Routing Metric: Advancements and Research in Energy-efficient Opportunistic Routing Metrics in Wireless Sensor Networks (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Wireless sensor network are of developing enthusiasm because of progressions in small scale electro mechanical frameworks, nanotechnology and propelled wireless communication systems. These headways offer ascent to assemble little sized sensor nodes which are of ease and can play out different functions at once. The numerous undertakings include gathering information from sending region, handling this information and transmitting the same toward the base station which is a framework preparing node. WSN contains such sort of sensor nodes with wireless radios. In this paper we study about the researches done in the field of new energy efficient opportunistic routing metric.